(untitled) - Stow, D. A. V.; 1961-; Packham, Chris; (Dorrik A. V.); Eales, Philip; Harvey, Derek; Funston, Gregory; Lacchia, Anthea (New York, NY, 2022)
"This breathtakingly beautiful book reveals the unique wonders of our planet, from core to atmosphere. Illustrated with detailed images of fascinating objects-- from colorful crystals to ancient fossils-- along with awe-inspiring landscape photography, it brings to life the story of Earth's past and the dynamic processes that shape its present."--
Keywords: Earth sciences; Earth sciences